2004
DOI: 10.1603/0022-2585-41.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance and Cross-Resistance in Alabama and Florida Strains ofCulex quinquefaciatus

Abstract: Insecticide resistance and cross-resistance was determined for three strains of Culex quinquefasciatus Say in the southeastern United States. HAmCq and MAmCq strains were collected in 2002 from Huntsville and Mobile, AL. The VBFmCq strain was collected in 1998 from Vero Beach, FL. VBFmCq, HAmCq, and MAmCq larvae showed resistance to permethrin with resistance ratios of 13, 100, and 940, respectively, compared with the susceptible S-Lab strain. Levels of resistance in HAmCq and MAmCq larvae were 200- and 830-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 27 publications
3
90
0
1
Order By: Relevance
“…The data extracted from the AQUIRE database consisted of results from laboratory experiments under a range of test conditions. Acute toxicity values might depend on the test conditions, such as the material type of the insecticide (e.g., active ingredient or formulation) 29) , the insect's growth stage, 30) and the sampling site [31][32][33] where test animals were collected. Owing to wide differences in test conditions between our study and previous studies, careful comparison of sensitivities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The data extracted from the AQUIRE database consisted of results from laboratory experiments under a range of test conditions. Acute toxicity values might depend on the test conditions, such as the material type of the insecticide (e.g., active ingredient or formulation) 29) , the insect's growth stage, 30) and the sampling site [31][32][33] where test animals were collected. Owing to wide differences in test conditions between our study and previous studies, careful comparison of sensitivities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data on insecticide use for vector control are extremely important to design appropriate pesticide management systems on judicious use, resistance management, and reduction of risks to human health and the environment (79). However, a recent global survey drew attention to critical deficiencies in the capacity to manage vector control insecticides.…”
Section: Impact Of Insecticide Resistancementioning
confidence: 99%
“…These studies have revealed that resistance to insecticides is decreased by piperonyl butoxide (PBO), the inhibitor of cytochrome P450 monooxygenases. In a series of studies in our laboratory designed to investigate how pyrethroid resistance develops, a house fly strain ALHF G0 and a mosquito strain HAmCq G0 were collected from sites in Alabama and further selected with permethrin for 6 and 8 generations, respectively, generating the strains of ALHF and HAmCq G8 (Liu and Yue 2000;2001;Liu et al 2004a;Xu et al 2006a;Li et al 2010). Both permethrin selected house fly and mosquito strains achieved very high levels of resistance compared with their parental strains.…”
Section: P450-mediated Pyrethroid Resistancementioning
confidence: 99%